Does public opinion affect air quality? Evidence based on the monthly data of 109 prefecture-level cities in China. (May 2018) - Zhang, Shengling; Li, Yue; Hao, Yu; Zhang, Yipeng
Abstract: In recent years, serious smog and haze have shrouded vast areas of northern and eastern China, which has drawn broad attention at home and abroad. Although China is an authoritarian country with strict media control, public opinion may still affect air quality by putting pressure on the local and central governments to enhance environmental protections. In this paper, the impact of public opinion on air quality in China is for the first time quantitatively examined. Specifically, the monthly average levels of the Air Quality Index (AQI) and the concentrations of several main air pollutants, such as PM2.5, PM10 and SO2, are utilized as indicators for air quality. Using a dataset consisting of 109 prefecture-level Chinese cities for the period between November 2013 and October 2016, the estimation results indicate that air pollution significantly affects public opinion on air quality, and the surge in public opinion on air pollution occurs more frequently in the winter. Public opinion seems to have a positive effect on the environment only in the short run: air quality tends to improve two months after the surge in negative public opinion. In general, public opinion about air pollution helps to improve air quality in China. Highlights: The impact of public opinion on haze pollution in China is investigated. A dataset consisting of 109 prefecture-level Chinese cities is employed. Public opinion has a positive effect on the environment only in the short run. There is a time lag between the surge in public opinion and improved air quality.